INFLUENCE OF GENDER ON LEARNING AND BEHAVIOURAL PERFORMANCES OF UNDERGRADUATE PRE-SERVICE TEACHERS USING MOBILE ASSISTED INSTRUCTION - Amosa Isiaka Gambari; Ramatu Ematum Umahaba; Mohammed Lawal Gwoza; Muhammed Saifullahi (MOJES: Malaysian Online Journal of Educational Sciences, 2026)
This study examines the influence of gender on the learning and behavioural performances of undergraduate pre-service teachers using mobile-assisted instruction. The study employed a Quasi-experimental design, using a pretest-posttest, non-equivalent, non-randomized control group. One hundred and sixteen pre-service teachers were sampled using stratified random sampling techniques. The data were collected using the treatment instrument (MAI), treatment instrument-course material (BCSM), Test instrument (CSPT), and Validation Test Questionnaire (MAIQ) for field trial validation. Pilot testing was conducted on thirty students, and a reliability coefficient of 0.87 was obtained. The data were analyzed using mean and standard deviation, while the Analysis of Covariance (ANCOVA) test was used to test the stated hypotheses at a 0.05 level of significance. The findings showed that: Hypothesis one was not rejected, the result shows that the medium of instruction produced no significant difference in the posttest reaction scores of students when the covariate effect (pretest) was controlled. Hypothesis two was rejected; there was a significant difference in the learning performance of male and female students. Also, Hypothesis three was rejected; the result shows that there was a significant difference in the behavioural performance of male and female students. Based on the findings, the following recommendations were made: Lecturers in higher institutions should be encouraged to use mobile learning to support their teaching. To achieve this, workshops/seminars should be organized specifically for the purpose of facilitating the use of mobile technology devices in teaching and learning; emphasis should be placed on making learning learner-centred.